Football Fan Aggression: The Role of Democratic Parenting and Emotion Regulation - Desy Maria Ulfa; Mujidin Mujidin; Ahmad Muhammad Diponegoro (Jurnal Psikologi TALENTA, 2022)
This study aims to empirically examine the relationship between democratic parenting and emotion regulation with the aggressiveness of soccer fans. The research subjects were students of class XI SMA Negeri 1 Sleman, totalling 71 students. The Likert model scale is the main instrument to obtain data on aggressiveness, democratic parenting, and emotion regulation. The data was then analyzed using multiple regression with the SPSS V26 program. The analysis results show that simultaneously there is a very significant relationship between democratic parenting and emotion regulation with aggressiveness (R = 0.604 with a sig. 0.000). While partially, democratic parenting with aggressiveness and emotion regulation with aggressiveness proved to have a very significant negative relationship (partial = -0.460 with sig. 0.000 level and partial = -0.315 with sig. 0.008). The contribution of democratic parenting to aggressiveness is more dominant (24%) than the contribution of emotion regulation to aggressiveness (12.4%). In conclusion, democratic parenting as an external factor from the family environment plays a vital role in controlling children's behaviour in adolescence (aggressiveness) than factors originating from within the child (emotion regulation).